2018
DOI: 10.1038/s41598-018-20018-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a biosynthetic gene cluster for the polyene macrolactam sceliphrolactam in a Streptomyces strain isolated from mangrove sediment

Abstract: Streptomyces are a genus of Actinobacteria capable of producing structurally diverse natural products. Here we report the isolation and characterization of a biosynthetically talented Streptomyces (Streptomyces sp. SD85) from tropical mangrove sediments. Whole-genome sequencing revealed that Streptomyces sp. SD85 harbors at least 52 biosynthetic gene clusters (BGCs), which constitute 21.2% of the 8.6-Mb genome. When cultivated under lab conditions, Streptomyces sp. SD85 produces sceliphrolactam, a 26-membered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…While recognizing that more mundane environments can contain novelty for the bioprospector (e.g. forest soil [73], street sediments [74]) we opine that the case for prioritizing extreme biomes is sound as it moves bioprospecting action away from well-probed terrestrial streptomycetes towards microbial communities that have evolved under harsh selective conditions during the course of which novel biochemistry has been generated [75]. As Rateb et al report [66], a total of 46 natural products representing diverse chemical classes have been isolated from Atacama Desert actinobacteria during the past 7 years.…”
Section: Is Focus On the Extremobiosphere Justified?mentioning
confidence: 93%
“…While recognizing that more mundane environments can contain novelty for the bioprospector (e.g. forest soil [73], street sediments [74]) we opine that the case for prioritizing extreme biomes is sound as it moves bioprospecting action away from well-probed terrestrial streptomycetes towards microbial communities that have evolved under harsh selective conditions during the course of which novel biochemistry has been generated [75]. As Rateb et al report [66], a total of 46 natural products representing diverse chemical classes have been isolated from Atacama Desert actinobacteria during the past 7 years.…”
Section: Is Focus On the Extremobiosphere Justified?mentioning
confidence: 93%
“…Both groups of BGCs are known to encode proteins involved in biosynthesis and the processing of secondary metabolites with various antibiotic activities [65]. In other microorganisms, NRPS are responsible for synthesis of compounds such as actinomycin, vancomycin, and coelibactin [66][67][68], and T1PKS produce compounds such as rapamycin, cyphomycin, and glutaramides [18,25,69]. On the other hand, phenotype fingerprinting using a microplate assay showed that the S-2 strain was susceptible to several antibacterial antibiotics targeting protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Testing multiple protospacers may also help when no genome editing is observed. Low and coworkers showed that only one out of five protospacers yielded the desired deletion of a polyketide synthase module in Streptomyces Sd‐85 (Low et al, ). Optimizing Cas expression through various strategies to balance transcription and translation efficiencies has been successful in alleviating nuclease‐induced toxicity in organisms, such as mycobacteria, cyanobacteria, and corynebacteria (Cho et al, ; Sun et al, ; Wendt, Ungerer, Cobb, Zhao, & Pakrasi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, sequence‐specific toxicity is observed for the catalytically dead spCas9 (dCas9) in Escherichia coli and can be alleviated by reducing dCas9 expression levels (Cui et al, ). In other contexts, even after a successful introduction of recombinant CRISPR‐Cas systems, no editing is observed in exconjugants expressing spCas9 and its guide RNA (Low et al, ). In E. coli , modifications induced by CRISPR‐Cas9 double‐stranded breaks are circumvented with RecA‐dependent repair (Moreb et al, ).…”
Section: Introductionmentioning
confidence: 99%